Analysis of the quality of broccoli leaf powder treated by blanching and drying - Hamid, Mansoor Abdul; Chong , Wan Ni; Hong, Yeap Chi; Mantony, Oslida; Devi, Mazarina; Soekopitojo, Soenar; Pratikto, Heri; Wibawa, Aji Prasetya; Sugiyanto, Sugiyanto (Agribusiness Department, Agriculture and Forestry Faculty, Universitas Sulawesi Barat, Indonesia, 2023)
Brassica oleracea L. italica, the scientific name for broccoli, is a vegetable that is frequently consumed for its florets, which have a number of health benefits. However, other portions of the plant, including the leaves, are almost always discarded despite being good for human health. The study was carried out with the purpose of investigating how the physicochemical characteristics of powdered broccoli leaves were affected by blanching and various drying techniques applied. Broccoli leaves were first blanched in hot water before being dried, which included sun drying, oven drying, cabinet drying, and vacuum drying. The findings demonstrated that blanching enhanced the powder's physical attributes while maintaining its phenolic and flavonoid contents. Blanching also reduced the breakdown of the chlorophyll content in all drying techniques, although this process made it harder to keep the goods' antioxidant function. In conclusion, vacuum drying method of blanched broccoli leaf powder showed the highest retention of physicochemical properties, phytochemical content, and antioxidant activity.